Recontextualizing Interfaith Dialogue as an Implementation of Religious Moderation in the Modern Era: A Study of the Online-Based Inclusive Movement - Ali Mursyid Azisi; Kunawi Basyir; Mohammad Najihuddin; Shofiatul Karimah; Ummu Hani Assyifa (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This article examines the importance of interfaith dialogue as a form of implementing religious moderation in the living space of modern society which is marked by the existence of social media. Dialogue between religions in order to build harmony that leads to peace and brotherhood is a must. Therefore, to achieve this the basic principle of maintaining ukhuwwah (brotherhood) is the key. Interfaith dialogue is not only important to be carried out face to face, but advances in technology have the opportunity to more easily interact via virtual with other religions to sow harmony. This article was written using a qualitative approach and using library research steps by placing books and journals as primary data, as well as writing from websites as supporting data. This article finds the conclusion that interfaith dialogue in multi-religious Indonesia is something that needs to be built in various spaces, including social media. The large diversity of religions has the potential to cause friction/conflict, but if the values of moderation are implemented properly by consistently building dialogue for the progress of the nation and harmony will avoid destruction. Other efforts that can be applied in the modern era are building moderate narratives on social media, building creative content, collaborating and continuing. Then later it will lead to harmony, equality, balance, peace, and away from tension.